IoT applications using blockchain and smart contracts - Roriz, Rui (2019)
Blockchain is a relatively new technology, initially created for the Bitcoin’s network to store transaction records happening in it. The system is redundant and distributed, making it difficult for fraudulent transactions. Beyond digital currencies, the blockchain concept has already demonstrated its potential in the insurance, health, digital identity, and many other areas. In order to deal with specific needs in those areas, a new technology has appeared – smart contracts – computational code programmed to meet and enforce certain conditions, like the ones seen in traditional contracts. Taking into account the benefits brought by blockchain and smart contracts, it is important to study their contributions to emerging technological solutions, like IoT (Internet of Things), in which security, connectivity and interoperability are major concerns. This paper aims to describe relevant blockchain and smart contract’s concepts, discussing their contribution to support and improve modern IoT solutions.